Mix design and performance analysis of asphalt concretes with electric arc furnace slag - Pasetto, M.; Baldo, N.
The paper presents the results of a laboratory study, aimed at verifying the possibility to use two particular typologies of electric arc furnace (EAF)steel slags, in substitution of the natural aggregates, in the composition of wearing course asphalt concrete for flexible pavements. The experimental research has been articulated in a preliminary study of the chemical, leaching, physical, and mechanical properties of the EAF steel slag, and in the following mix design and performance characterisation of the bituminous conglomerates, through gyratory compaction tests, permanent deformations tests, Stiffness Modulus tests at various temperatures, fatigue tests and indirect tensile strength tests. All the mixtures with EAF slag have satisfied the requisites for acceptance in the road sector technical standards, thus resulting as suitable for use in the construction of road infrastructures, moreover presenting higher mechanical characteristics than those of the corresponding asphalts with full natural aggregate.
Keywords: STEEL SLAG; LEACHING; ASPHALT CONCRETE; STIFFNESS; RUTTING; FATIGUE RESISTANCE; MOISTURE DAMAGE